Optimizing Low Speed VoIP Network for Rural Next Generation Network (R-NGN) - Yoanes Bandung; Carmadi Machbub; Armein Z. R. Langi; Suhono H. Supangkat (Journal of ICT Research and Applications, 2007)
In this paper, we identify some impairments in the Voice over Internet Protocol (VoIP) networks and quantify the levels of voice quality. We propose an optimization model to maximize number of calls in low speed network for Rural Next Generation Network (R-NGN) while maintaining a minimum level of voice quality. The model is based-on Extended E-model to select parameters like voice coder, packet loss level, jitter buffer size, and network utilization. The optimum VoIP access network is achieved by applying G.723.1 5.3 kbps voice coder, packet loss level less than 1%, jitter buffer 50 ms, and network utilization less than 85%.